Work-life policies in Great Britain: What works where and how? - UK. Department for Business, Enterprise & Regulatory Reform; Nadeem, Sadia; Metcalf, Hilary (London, 2007)
"Employment Relations Research Series no 77. Examines the provision and effects of work-life balance policies, using data from the 2004 workplace employment relations survey (WERS)."